Pharmacological Regulation of Ischemia-Activated Pericyte Reprogramming and Differentiation for Post-Stroke Regeneration and Recovery - Lui, Margarita (Université d'Ottawa / University of Ottawa, 2022)
Direct in vivo cellular reprogramming offers the potential for local neural replacement to promote post-stroke neural regeneration and recovery. Pericytes are perivascular cells involved in blood-brain barrier maintenance under physiological conditions but are reprogrammed into multipotent induced neural progenitor cells (i-NPCs) in response to ischemia. The atypical protein kinase C (aPKC)-CREB binding protein (CBP) pathway regulates ischemia-activated pericyte (a-pericyte) reprogramming and neuronal differentiation. Our previous work showed that the pathway inhibitor compound C (CpdC) facilitated a- pericyte reprogramming into i-NPCs in culture, and that monoacylglycerol lipase (Mgll) inhibitor JZL184 was able to promote NPC differentiation to generate newborn neurons by mimicking pathway activation. In this regard, we propose to use acute CpdC treatment followed by chronic JZL184 treatment to enhance reprogramming of a-pericytes into i-NPCs and subsequently promote their neuronal differentiation, ultimately improving post-stroke functional recovery. Using the endothelin-1 (ET-1)/L-NAME ischemic stroke model in a pericyte lineage tracing transgenic mouse line, I characterized the ability of a-pericytes in the ischemic lesion site to generate neural (i-NPC, newborn neurons) and non-neural (microglia and fibroblasts) cell types. The CpdC+JZL184 treatment had early effects on enhancing a- pericyte reprogramming efficiency to produce i-NPCs at 7 days post-stroke and promoting their differentiation to generate neuroblasts at 14 days post-stroke. However, it did not affect stroke volume and produced minimal alterations to the pattern of post-stroke motor function recovery. Interestingly, I discovered a novel role of tamoxifen treatment prior to stroke in regulating reprogramming of a-pericytes and efficacy of compound C treatment. These studies inform the necessity of optimization of drug delivery for better control over the timing and duration to directly target in vivo i-NPC reprogramming and reveal a novel pharmacological paradigm to control the aPKC-CBP pathway.
Keywords: Stroke; Regeneration; Cellular reprogramming; Pericytes